Recent advances in personalizing rheumatoid arthritis therapy and management. (March 2009) - Hughes, Laura B; Danila, Maria I; Bridges, S Louis
Rheumatoid arthritis (RA) is a chronic, systemic, inflammatory disorder characterized by synovial inflammation in diarthrodial joints. There are significant interindividual variations in the degree of inflammation, disease course and the rate of joint progression in patients with RA. A number of clinical, serological, environmental and genetic severity factors have been identified in patients with RA and can be used to help guide treatment. Therapeutic options for RA have significantly expanded in the last decade and now include both synthetic disease-modifying antirheumatic drugs as well as biologic disease-modifying antirheumatic drugs. Owing to the variety of new drugs, their cost and incomplete information on side effects, markers of treatment response are needed. The study of treatment-specific genetic and protein biomarkers of response and toxicity in RA has produced exciting, yet inconsistent, results. Large scale genetic and proteome studies, which can now be performed at a relatively low cost, will likely broaden the scope and significance of biomarker studies in RA. Integration of these results into clinical practice will vastly improve our ability to provide safe and effective therapy to individuals with RA.